Optimizing Fruit-Thinning Strategies in Peach (Prunus persica) Production - Mary Sutton; John Doyle; Dario Chavez; Anish Malladi (Horticulturae, 2020)
Fruit size is a highly valued commercial trait in peach. Competition among fruit and among other sinks on a tree reduces potential growth rate of the fruit. Hence, crop-load management strategies such as thinning (removal of flowers or fruit) are often practiced by growers to optimize fruit size. Thinning can be performed at bloom or during early fruit development and at different intensities to optimize fruit growth responses. Responses to thinning may be cultivar and location specific. The objective of the current study was to fine-tune thinning strategies in the southeastern United States, a major peach producing region. Timing and intensity of thinning were evaluated across multiple cultivars over three years. Thinning at bloom or at 21 d after full bloom (DAFB) improved fruit size in comparison to unthinned trees in ‘Cary Mac’ and ‘July Prince’, respectively, in one year. Bloom-thinning reduced fruit yield (kg per tree) in the above cultivars in one year, suggesting that flower thinning alone may not be a viable option in this region. Intensity of thinning, evaluated as spacings of 15 cm and 20 cm between fruit, did not differentially affect fruit weight or yield. However, fruit diameter decreased quadratically with increasing fruit number per tree in ‘Cary Mac’, ‘July Prince’ and ‘Summer Flame’. Similarly, fruit weight decreased quadratically in response to increase in fruit number per tree in ‘Cary Mac’ and ‘July Prince’. Further, yield-per-tree decreased with increasing fruit size in ‘Cary Mac’ and ‘July Prince’. Importantly, these relationships were cultivar specific. Together, the data suggest that achieving a target fruit number per tree is an effective strategy for crop-load management to optimize fruit size in southeastern peach production. The target fruit number per tree may potentially be achieved through a combination of flower and fruit-thinning during early fruit development. Such an approach may provide flexibility in crop-load management in relation to adverse weather events.